Advances in surgical treatment of ulcerative colitis associated colorectal cancer - He-Yuan NIU; Gang LIU (Yixue xinzhi zazhi)
Ulcerative colitis (UC) is a chronic, non-specific inflammatory disease of the intestinal tract, the etiology of which remains uncertain. Ulcerative colitis associated colorectal cancer (UC-CRC) stands as one of the most severe complications for UC patients, presenting as a significant cause of mortality. Due to its distinctive clinical features, the indications of surgery, optimal timing, surgical approach, and perioperative management differ from those of sporadic colorectal cancer. This article aims to provide a comprehensive review of the current status of surgical treatments for UC-CRC and perioperative management, serving as a valuable reference for clinical practice.